Pengaruh Brand Ambassador Boygoup Bangtan Sonyeodan Dan Minat Beli terhadap Keputusan Pembelian Menggunakan Market Place Tokopedia - Nabila Kausarani; Eman Sulaeman (Universitas Batanghari, 2023)
This study was conducted to determine how big the relationship and influence of brand ambassadors and buying interest on purchasing decisions. The object used in this study is the Tokopedia marketplace user community. This study uses a quantitative type with descriptive and verification methods. The data collection technique used is the questionnaire technique, literature study and internet research. Partial influence of Brand Ambassador on Purchase Decision is 8.1% while Buying Interest on Purchase Decision has a much greater influence, which is 30.2%. Simultaneously, the total influence of Brand Ambassador and Buying Interest on Purchase Decisions is 25.2% while the remaining 74.8% is another influence that is not measured in this study.